Numerical evaluation of the thermal performance of a near-surface earth-to-air heat exchanger with short-grass ground cover: A parametric study. (May 2021) - Pakari, Ali; Ghani, Saud
Highlights: Near-surface earth-to-air heat exchanger was modeled using CFD simulations. Variations of soil temperature and thermal conductivity with depth were considered. Results showed good agreement between simulations and measurements within ±0.5 °C. Effect of various parameters on the heat exchanger performance was investigated. Soil thermal conductivity significantly affected the heat exchanger performance. Abstract: High energy consumption and increasing energy cost have encouraged investment in energy efficiency. In hot areas, like the Middle East, the share of space cooling accounts for most of the total energy use in buildings. Earth-to-air heat exchangers represent an energy-efficient and environmentally friendly cooling technique. An earth-to-air heat exchanger buried near the ground surface with short-grass cover, which lowers the soil temperature by evapotranspiration, is an alternative to conventional deep buried types. In this study, a steady three-dimensional numerical model of this earth-to-air heat exchanger was developed by considering the conservation of mass, momentum, energy, and species. Soil temperature and moisture content measurements were used as boundary conditions for the model. In addition, the variations of soil temperature and thermal conductivity with depth were considered in the model. Numerical predictions of temperature matched experimental measurements within ±0.5 °C. Using the validated numerical model, the effect of inlet air temperature, airflow rate, tube length, material, wall thickness, and soil thermal conductivity on the earth-to-air heat exchanger thermal performance was investigated. Increasing the airflow rate and tube length resulted in an asymptotic increase and decrease in the earth-to-air heat exchanger outlet temperature, respectively. By increasing the tube wall thickness from 1 to 10 mm, the outlet temperature for an aluminum tube remained unchanged, while for PE and PVC tubes, the outlet temperature increased by about 1.1 and 2.2 °C, respectively. By increasing the soil thermal conductivity from 1 to 5 W m −1 K −1 the outlet temperature decreased by about 4.4 °C.